Women's workforce participation and spousal violence: Insights from India - Arpita Biswas; Anjana Thampi (University of Massachusetts, Department of Economics, 2021)
Intimate partner violence is a serious form of unfreedom inflicted on women across the world. How does the incidence of such violence vary with women's workforce participation - a factor that is supposed to enhance their economic well-being? Our study examines this relationship using a nationally representative dataset from India. Given vast heterogeneity among Indian women, we investigate how this link varies by their class and socio-religious identities. Treating women's employment as endogenous, we find that it is associated with a significantly higher probability of reported spousal violence for women from all wealth quintiles except the topmost and across all social groups. Moreover, the reported risks are found to be relatively higher for disadvantaged groups. We hypothesize that these findings could be explained through the backlash effect arising from two sources: the perceived violation of socio-cultural norms by employed women and the double burden of reproductive and market work on them.
Keywords: B54; J12; J16; 330; Spousal violence; women's employment; reproductive labor; India; inequalities; intersectionality